Empathy and the art of Leonardo da Vinci - Mansur, Samira Schultz; DeFelipe, Javier (Frontiers in Psychology, 2024)
Knowledge about empathy is part of the study of artistic expressions, among which stand out works of personalities such as the Renaissance polymath Leonardo da Vinci, who was concerned with the connection between science and art during his creative research full of imagination and sensitivity to nature and human anatomy. The word empathy emerged among critics of German art as the term einfühlung, which was used within the aesthetic bias by philosophers and art historians. It emphasized the idea that a viewer perceiving an object could establish a link between it and themselves, projecting the object ‘into themselves’. That is, the artwork could be experienced by the observer as if the viewer belonged predominantly to the object, in such a way that its characteristics could be actually felt through the expression of emotions, feelings and thoughts. This analysis of art appreciation required a great deal of knowledge and contemplation of nature, as understood by the German Romanticists, who had enormous admiration for da Vinci and his universal and systematic mind—a mind which reacted against formalisms, building his intellectual and sensory systems based on both his observation of nature and his own criteria. In particular, the art of painting for Leonardo was a way to demonstrate a mental discourse, just as the most important aspect of human portraits is to represent—in gestures and facial expressions—the states of mind and emotions. These are facts that German Romanticists tried to explain as the relationship between empathy and a work of art. The present manuscript aims to describe empathy from an artistic view, considering the roots of this word in German Romanticism; to comment about Leonardo da Vinci and the expression of art in the Renaissance; and, finally, to discuss the expression of his art in relation to empathy.